总述:本次共解1题。其中
☆算术计算1题
〖1/1算式〗
作业:求算式 -(1/(2*200*10^(-6)))+-sqrt((1/(2*200*10^(-6)))^2-(1/(0.64*10^(-6)))) 的值.
题型:数学计算
解:
-(1/(2*200*10^(-6)))+-sqrt((1/(2*200*10^(-6)))^2-(1/(0.64*10^(-6))))
=-(1/(2*200*10^(-6)))+-sqrt((1/(2*200*10^(-6)))^2-(1/(0.64*10^(-6))))
=-(1/0.0004)+-sqrt((1/(2*200*10^(-6)))^2-(1/(0.64*10^(-6))))
=-2500+-sqrt((1/(2*200*10^(-6)))^2-(1/(0.64*10^(-6))))
=-2500+-sqrt((1/(2*200*10^(-6)))^2-(1/(0.64*10^(-6))))
=-2500+-sqrt((1/0.0004)^2-(1/(0.64*10^(-6))))
=-2500+-sqrt(2500^2-(1/(0.64*10^(-6))))
=-2500+-sqrt(2500^2-(1/(0.64*10^(-6))))
=-2500+-sqrt(2500^2-(1/0.000001))
=-2500+-sqrt(2500^2-1000000)
=-2500+-sqrt5250000
=-2500.000000+-2291.287847
=-4791.287847 答案:-(1/(2*200*10^(-6)))+-sqrt((1/(2*200*10^(-6)))^2-(1/(0.64*10^(-6))))=-4791.287847你的问题在这里没有得到解决?请到 热门难题 里面看看吧!